Double-poling biomechanics of elite cross-country skiers: flat versus uphill terrain - Stöggl, T. L.; Holmberg, H. C. (Medicine & Science in Sports & Exercise, 2016)
Introduction: In light of the recent revolutionary change in the use of the double-poling (DP) technique in cross-country skiing, our purpose was to compare the associated kinetics and kinematics on flat (DPflat) and uphill terrain (DPup), as well as to identify factors that determine performance.